The Role of the Taklim Council in the Development of Islamic Education - Sukirman Sukirman; Firman Firman; Dodi Ilham (Journal of Indonesian Islamic Studies, 2021)
This research formulate the subject about the problem which is: What is Taksim's ceremony have Islamic education development role at Toraja North? How methods of ceremony education construction take at Toraja North? This research is an observational qualitative who utilizes pedagogics approaching, psychological, sociological, and normative theological. Data source which is stemmed primary data from Mapenda, Taklim's Ceremony administrator, Religion figure, and Islam Extension Agent, meanwhile secondary data taken from by bearing aught document it is with research. The instrument that is utilized in gathering data is functioning alone writer establishes and chooses the informant as the source of data, analysis is data, paraphrasing data, and instrument in gathering data is observation, interview, and documentation. Observational results and analysis conclude Taksim's ceremony role in developmental Islamic education: 1). Education that performed by taklim's ceremony at Toraja North corresponds to education concept along the body. Ages unacquainted education and were in force of coming into the world to puff out. taklim's ceremony education at North Toraja constitutes education to get society basis and gives education to society on all age levels. Therefore, ta's Ceremony education taklim at orth Toraja Nget has been utilized medium for I apply Islamic teaching points, so fade-proof Islam points with other points unsuitably. 2) learning methods that are utilized on santri children cover methodic discourse, question-answer, story, matzah, to inuring a figure of speech. The discourse method is utilized to enlighten the material reads and writes the Koran. On the same chance, the teacher also gives chance for santri for asking to chastened material. In addition, the teacher also utilizes that story method material which is taught gets is prey to by santri and stimulates santri to notice chastened material.